Co-pyrolysis technology for enhancing the functionality of sewage sludge biochar and immobilizing heavy metals. (March 2023) - Fan, Zeyu; Zhou, Xian; Peng, Ziling; Wan, Sha; Gao, Zhuo Fan; Deng, Shanshan; Tong, Luling; Han, Wei; Chen, Xia
Abstract: Sewage sludge (SS) is a frequent and challenging issue for countries with big populations, due to its massive output, significant hazard potential, and challenging resource utilization. Pyrolysis can simultaneously realize the reduction, harmlessness and recycling of SS. Co-pyrolysis offers a wide range of potential in terms of increasing product quality and immobilizing heavy metals (HMs), thanks to its capacity to use additives to address the mismatch between SS characteristics and pyrolysis. High-value utilization potential of SS biochar is the key to evaluating the advancement of treatment technology. A further requirement for using biochar resources is the immobilization and bioavailability reduction of HMs. Due to the catalytic and synergistic effects in the co-pyrolysis process, co-pyrolysis SS biochar exhibits enhanced functionality and has been applied in soil improvement, pollutant adsorption and catalytic reactions. This review focuses on the research progress of different additives in improving the functionality of biochar and influencing the behavior of HMs. The key limitation and challenges in SS co-pyrolysis are then discussed. Future research prospects are detailed from seven perspectives, including pyrolysis process optimization, co-pyrolysis additive selection, catalytic mechanism research of process and product, biochar performance improvement and application field expansion, cooperative immobilization of HMs, and life cycle assessment. This review will offer recommendations and direction for future research paths, while also assist pertinent researchers in swiftly understanding the current state of SS pyrolysis research field. Graphical abstract: Image 1 Highlights: SS disposal technologies are compared and co-pyrolysis's advantages are emphasized. The catalytic and synergistic effects of SS co-pyrolysis are summarized. The effects of additives on biochar functionality and HMs behavior are discussed. Limitation and challenges in SS co-pyrolysis are discussed. The prospects of future co-pyrolysis research are recommended.